Miles Buchan: capstone - Buchan, Miles, artist (Colorado State University. Libraries, 2022)
The artist's statement: My work serves as an exploration of my personal condition and experience with extreme light sensitivity and "legal blindness". Between the binary of the sighted and the blind exists a spectrum of perception, which drastically effects lived experiences. As an individual with Oculocutaneous Albinism 1, my sight varies and depends greatly upon my surrounding environment, particularly when it comes to light, movement, and scale. This has impacted my life beyond my own understanding, as it is all that I've known. As I learn more about myself and the world around me, I begin to question how deep these implications lie. I've addressed and confronted this reality in both scale and material to include paintings, sculptures, experimental drawings, and installations. For drawings and sculptures which exist three dimensionally, I am interested in exploring and manipulating the effects of light, physical space, and orientation to engage with viewers own senses. For two-dimensional work I focus on some of the same qualities through composition. Utilizing color, contrast, and pattern to create a sense of space which interacts with the viewers perception to create meaning. As a visual artist working and living with a visual disability my style, process, and finalized work are all informed by both preference and ability. Whether I'm creating something meant to be representationally naturalistic or fully abstract, I must work and negotiate with my eyes, sight, and senses throughout.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: drawing